Uma eficiente abordagem num?rica para a lineariza??o de amplificadores de pot?ncia em RF com os recursos da t?cnica de pr?-distor??o digital - Silva, Marcos Paulo de Souza (2004)
The non-linearization of devices for certain applications is undesirable and they occur in many electronic types of equipment for Telecommunications Systems. In our specific case they are present in the transmission of Digital TV signals strongly dependent of the RF power amplifiers. Due to the nonlinear behavior one becomes necessary to accomplish previous studies of the devices and circuits that carry through the linearization. The main focus of this dissertation besides the theory was the development of an experimental practical part, with the creation of a prototype. This, together with the use of some numerical methods applied to the resources of the digital predistortion; permit us to set an efficient linearization of the TV signals. This process starts on the analog models and have nowadays a great development with the digital one.